Systematic Literature Review of Critical Success Factors in Online Advertising - Eryc Eryc (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING, 2022)
Online Digital advertising is one method that is increasingly popular in the era of digital transformation that is currently underway. This causes companies to compete in developing digital business strategies, especially in terms of marketing. Online advertising aims to be effective in a cost-effective manner to effectively reach the intended target market segments. Previously, there had been a lot of research on online advertising that could help research or companies in developing their marketing strategies. It is necessary to review the literature on online advertising from these previous studies so that information is classified and categorized systematically. This study aims to provide information by conducting a Systematic Literature Review (SLR) on the latest research on online advertising from 2015 to 2020 in order to find out online advertising indicators that are still relevant and objective to achieve marketing strategy goals. Systematic Literature Review (SLR) approach which includes research questions, journal sources, preparation. Researchers analyzed the factors that determine success in the latest online advertising using the Systematic Literature Review (SLR) method. This research is useful for reviewing academic literature for online advertising research and as a reference for companies in increasing advertising effectiveness as part of a business strategy or marketing advantage in market competition.